Peningkatan keterampilan berbicara siswa SD melalui program SAPU TUWA - Munadah, Siti; Ibda, Hamidulloh; Fadloli Al Hakim, Muhammad (Al-Azkiya: Jurnal Pendidikan MI/SD, 2022)
Third-grade students of Jogoyasan State Elementary School, Magelang have less confidence when speaking in front of the class and when the teacher asks questions. Poetry is a way for students to express themselves to improve their speaking skills. The purpose of this study was to determine the speaking skills of third-grade students of Jogoyasan State Elementary School through the SAPU TUWA (One Poem One Student) program. This action research uses the Kemis & Taggart model which consists of four stages (planning, action, observation, and reflection). The object of the research was 31 students (21 boys and 10 girls). Data were obtained through observation, interviews, student journals, and teacher journals analyzed by data reduction and conclusion drawing, questionnaires, and poetry reading tests. The results showed that the SAPU TUWA program helped improve speaking skills. The indicators of each cycle include improvements in several ways: (1) the total score of the cycle I was 2,018.75 to 2,550 in cycle II (2) the average score of the cycle I was 65.12 to 85.25 in cycle II (3) the minimum score in cycle I was 50 to 62.5 in cycle II (4) the maximum score in cycle I was 75 to 87.5 in cycle II (5) increased student motivation seen from participation and positive responses during the SAPU TUWA program